Dietary Macroalgae Saccharina japonica Ameliorates Liver Injury Induced by a High-Carbohydrate Diet in Swamp Eel (Monopterus albus) - Yu, Chuanqi; Wang, Lu; Cai, Wanghe; Zhang, Wenping; Hu, Zhonghua; Wang, Zirui; Yang, Zhuqing; Peng, Mo; Huo, Huanhuan; Zhang, Yazhou; Zhou, Qiubai (Frontiers in Veterinary Science, 2022)
High-carbohydrate diet lower the rearing cost and decrease the ammonia emission into environment, whereas it can induce liver injury which can reduce harvest yields and generate economic losses in reared fish species. Macroalgae Saccharina japonica (SJ) has been reported to improving anti-diabetic, but the protective mechanism of dietary SJ against liver injury in fish fed high-carbohydrate diet is not reported. Therefore, an 56d nutritional trial was designed through swamp eel, which were respectively fed with the normal diet (20% carbohydrate, NC), high carbohydrate diet (32% carbohydrate, HC), and HC diet supplemented with 2.5% SJ (HC-S). Although HC diet promoted growth and lowered feed coefficient (FC), it increased hepatosomatic index (HSI) when compared with NC diet in this study. However, SJ supplementation increased iodine contents in muscle and improved liver injury-related parameters, such as decreasing HSI, serum glucose (GLU), bile acid (BA) and alanine aminotransferase (ALT), and hepatic glycogen and BA. Consistently, histological analysis showed that SJ reduced the area of hepatic lipid droplet, glycogen and collagen fiber (P<0.05). Thoroughly, the underlying protective mechanisms of SJ supplementation against HC-induced liver injury were studied by liver transcriptome sequencing coupled with pathway analysis. The KEGG pathway enrichment analysis of the differentially expressed genes (DEG) indicated that hepatitis C, primary bile acid biosynthesis and drug metabolism - cytochrome P450 were the three main metabolic pathways altered by SJ supplementation when compared with the HC group. Moreover, the BA-targeted metabolomic analysis of the serum BA found that SJ supplementation decreased taurohyocholic acid (THCA), taurochenodeoxycholic acid (TCDCA), taurolithocholic acid (TLCA), nordeoxycholic acid (NorDCA), and increased ursocholic acid (UCA), allocholic acid (ACA) and chenodeoxycholic acid (CDCA). In particular, the higher UCA, ACA and CDCA regulated by SJ were associated lower liver injury. Overall, these results indicate that SJ can be recommended as functional feed additives for the alleviation of liver injury in swamp eel fed high-carbohydrate diet.